The Impact of School Principals’ Practice of Re-Engineering Administrative Processes on Achieving Quality Assurance Standards from the Point of View of Educational Supervisors -An Empirical Study on the public schools in Kasbah Brigade- - Liswi, Wafa' Mohamad (Journal of Educational and Psychological Sciences, 2020)
This study aimed to identify the impact of school principals’ practice of re-engineering administrative processes on achieving quality assurance standards from the point of view of educational supervisors in the Kasbah Brigade. A survey method was used. The sample consisted of (42) supervisors. The results of the study showed that the degree of practitioners of public schools to re-engineering administrative processes from the point of view of educational supervisors in the Kasbah Brigade was high. Furthermore, the degree of achieving the quality assurance standards from the point of view of the educational supervisors in the Kasbah Brigade was moderate. The study recommended that the principal should pay attention to continuously improve the administrative processes in all its aspects and devise new ways to manage the school and perform its various tasks.